Shock parameters and shock index during severe post-partum haemorrhage and implications for management: a clinical study. (2nd January 2020) - Maneschi, Francesco; Perrone, Seila; Di Lucia, Alessandra; Ianiri, Palmiero
Abstract: The aim of this study was to report the association between shock severity, laboratory parameters and treatment in patients with severe post-partum haemorrhage (PPH) requiring the transfusion of ≥4 blood unit. Patients were divided into two groups: (1) conservative therapy and (2) emergency post-partum hysterectomy. The aggressive decision was always shared by two consultants. Out of 26, 094 deliveries, severe PPH occurred in 34 (0.13%) women, emergency post-partum hysterectomy was required in 13 (0.05%), while 21 (0.08%) were treated conservatively. Grade of shock, shock index (SI) and the number of blood units transfused were significantly higher in the hysterectomy group. No statistically significant difference among the two groups was observed for haemoglobin and coagulation results. The severity of shock was associated with the therapeutic choice in the treatment of severe PPH. Therefore, grade of shock and SI should be taken into consideration by the leading obstetrician in the decision making process toward the emergency hysterectomy. Impact Statement: What is already known on this subject? Primary post-partum haemorrhage (PPH) is the leading cause of maternal death in developing and industrialised countries. Emergency post-partum hysterectomy is considered a life-saving procedure performed when the women is experiencing a life-threatening haemorrhage. What the results of this study add? Therapeutic dichotomy between conservative and aggressive approach in severe PPH has not been defined, in particular emergency post-partum hysterectomy timing. Shock index (SI) has been proposed as an indicator of adverse maternal outcome. However, the association between shock parameters and advanced treatment modalities has not yet been reported. In our study, grade of shock, SI and the number of blood units transfused were significantly higher in the patients which needed hysterectomy suggesting that it may have a role in the decision making among conservative and aggressive treatment. No statistically significant difference was observed for haemoglobin and coagulation results. What the implications are of these findings for clinical practice and/or further research ? Grade of shock and SI should be taken into consideration in the decision making process toward the emergency hysterectomy in severe PPH. The choice between conservative and aggressive treatment should be based on hemodynamic parameters that may represent, in more accurate way, the severity of blood loss. Nevertheless, these data need further confirmation in a larger study.